2017
DOI: 10.1039/c7ta02319g
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion-templated, macroporous hydrogels for enhancing water efficiency in fighting fires

Abstract: High internal phase emulsion templated, interconnected macroporous hydrogels with rapid absorption, high and tunable water uptakes were fabricated for enhancing water efficiency in extinguishing fires and preventing combustible objects from burning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…After ten cycles' use, the porous structure and surface composition of HO‐35 were well preserved (Figure S5a, Supporting Information). No significant change in the interconnected porous structure was observed, and this is similar to the previous observation from hydrogel polyHIPEs . The surface composition revealed by EDS showed that all the elements were presented and the elemental contents kept almost unchanged (Figure S5b, Supporting Information).…”
Section: Methodssupporting
confidence: 88%
“…After ten cycles' use, the porous structure and surface composition of HO‐35 were well preserved (Figure S5a, Supporting Information). No significant change in the interconnected porous structure was observed, and this is similar to the previous observation from hydrogel polyHIPEs . The surface composition revealed by EDS showed that all the elements were presented and the elemental contents kept almost unchanged (Figure S5b, Supporting Information).…”
Section: Methodssupporting
confidence: 88%
“…The masses of the PM‐ X ‐ Y (except PM‐80‐50) were obviously higher than the corresponding total masses of mannitol and polyHDI. P‐123 was reactive in step‐growth polymerization through the reaction between hydroxyl groups of P‐123 and isocyanate groups of polyHDI, although it is usually inert during free‐radical polymerization for PH synthesis and can be removed through extraction . Once P‐123 is covalently incorporated into the macromolecular structures of the PM‐ X ‐ Y , it is unlikely to be removed through extraction.…”
Section: Resultsmentioning
confidence: 99%
“…P-123 was reactive in step-growth polymerization through the reaction between hydroxyl groups of P-123 and isocyanate groups of polyHDI, although it is usually inert during free-radical polymerization for PH synthesis and can be removed through extraction. 13,34 Once P-123 is covalently incorporated into the macromolecular structures of the PM-X-Y, it is unlikely to be removed through extraction. To reflect the P-123, the yields of the PM-X-Y were calculated based on the total masses of mannitol, polyHDI, as well as P-123, and the yields were still quite high, ranging from 90% to 94% ( Table 2), indicating that most P-123 was covalently incorporated into the PM-X-Y.…”
Section: Yield Density and Macroporous Structuresmentioning
confidence: 99%
See 2 more Smart Citations